Analysis of the influence of the characteristics of the environment on the time of pedestrian transhipment in a multimodal transport using the social force model - Asenjo, Christian (2020)
El texto completo de este trabajo no está disponible en el Repositorio Académico UPC por restricciones de la casa editorial donde ha sido publicado.